Katabasis : a novel [large type] - Kuang, R. F. (Rebecca F.) (William Morrow Large Print, 2025)
"Alice Law has only ever had one goal: to become one of the brightest minds in the field of Magick. She has sacrificed everything to make that a reality: her pride, her health, her love life, and most definitely her sanity. All to work with Professor Jacob Grimes at Cambridge, the greatest magician in the world. That is, until he dies in a magical accident that could possibly be her fault. Grimes is now in Hell, and she?s going in after him. Because his recommendation could hold her very future in his now incorporeal hands and even death is not going to stop the pursuit of her dreams"--Provided by publisher.